Advantages of a P-element construct containing MtnA sequences for the identification of patterning and cell determination genes in Drosophila melanogaster. - Faucheux, M.; Netter, S.; Bloyer, S.; Moussa, M.; Boissonneau, E.; Lemeunier, F.; Wegnez, M.; Theodore, L. (Molecular Genetics and Genomics, 2001)
The P[MTW] transposon carries a functional MtnA (metallothionein) gene and a miniwhite reporter gene. When P[MTW] was transformed into Drosophila, many lines were found to show position-dependent expression patterns of the miniwhite or the MtnA transgene. Identification of several of the target genes indicated that this construct behaves as an enhancer or silencer trap. For instance, expression of at least one reporter transgene was shown to correlate with that of the endogenous gene in the case of insertions in Ultrabithorax, four-jointed, and the iroquois complex. The frequency of patterns recovered with P[MTW] is higher than that reported for P[LacW], suggesting that P[MTW] has unusual properties. The possibility of biased insertion of P[MTW] was assayed by screening a sample of 66 MTW lines for modifiers of the extra sex comb phenotype caused by a hypomorphic allele of polyhomeotic. Seven modifiers were recovered, which could be ranked in two classes: genes involved in leg morphogenesis (including four-jointed and spitz), and genes of the Polycomb- or trithorax-Group, including trithorax and batman, a new gene which encodes a product with a BTB/POZ domain. Taken together, these results indicate that P[MTW] allows the tagging of patterning and cell determination genes, and thus provides a useful tool for identifying new developmental functions.